Ubiquitin-specific peptidases in lymphoma: a path to novel therapeutics - Maryam Samareh Salavatipour; Shirin Tavakoli; Aram Halimi; Aram Halimi; Shima Tavoosi; Amir-Hossein Baghsheikhi; Abdolkarim Talebi-Taheri; Mehdi Niloufari; Zahra Salehi; Javad Verdi; Soheila Rahgozar; Alireza Mosavi-Jarrahi; et al. (Frontiers in Pharmacology)
BackgroundUbiquitin-specific peptidases (USPs), also known as deubiquitinating enzymes (DUBs), play a crucial role in maintaining cellular homeostasis by selectively removing ubiquitin molecules from targeted proteins. This process affects protein stability, subcellular localization, and activity, thereby influencing processes such as DNA repair, cell cycle regulation, and apoptosis. Abnormal USP activities have been linked to various diseases, including cancer. Emerging evidence in lymphoma studies highlights the significance of USPs in controlling signaling pathways related to cancer initiation and progression and presents them as potential therapeutic targets.AimThis study aimed to elucidate the multifaceted roles of USPs in lymphoma.MethodsThis systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles published in English up to May 2023 were retrieved from PubMed, Web of Science, and Scopus. The inclusion criteria focused on studies investigating the role of USPs in lymphoma cancer, involving human subjects or relevant lymphoma cell lines, exploring molecular mechanisms and signaling pathways, and assessing diagnostic or prognostic value.ResultsAfter the selection process, 23 studies were selected for analysis. USPs were found to affect various aspects of lymphoma development and progression. Specific USPs were identified with roles in cell-cycle regulation, apoptosis modulation, drug resistance, DNA repair, and influence of key oncogenic pathways, such as B cell receptor (BCR) signaling.ConclusionThis systematic review underscores the emerging role of USPs in lymphoma and their potential as therapeutic targets. Inhibitors of USPs, such as USP14 inhibitors, show promise in overcoming drug resistance. The dynamic interplay between USPs and lymphoma biology presents an exciting opportunity for future research and the development of more effective treatments for patients with lymphoma. Understanding the intricate functions of USPs in lymphoma offers new insights into potential therapeutic strategies, emphasizing the significance of these enzymes in the context of cancer biology.